Intersections of Gender and Genre: Sexualizing the Puella in Roman comedy, lyric and elegy - Judith P. Hallett (Eugesta, 2013)
My paper examines the use of the Latin diminutive noun puella, literally meaning “sexually immature” young girl, in Roman comedy, lyric and elegy. It considers how and why Catullus, Horace and the Augustan love elegists employed this noun for mature women they depict as sexually active and emotionally valued. Its analysis builds upon and critiques two earlier linguistic studies: one on the nouns puella and virgo, the other on puella as a term for “prostitute”. By so doing, it argues for the importance of analyzing Latin texts concerned with gender issues through traditional philological as well as innovative theoretical lenses.